2023
DOI: 10.3389/fnut.2023.1149137
|View full text |Cite
|
Sign up to set email alerts
|

Extraction, structural characterization, and antioxidant activity of polysaccharides derived from Arctium lappa L.

Abstract: IntroductionArctium lappa L. root has high nutritional and medicinal values and has been identified as a healthy food raw material by the Ministry of Health of the People's Republic of China.MethodsIn the present study, an aqueous two-phase system (ATPS) of polyethylene glycol (PEG)-(NH4)2SO4 was used to extract Arctium lappa L. polysaccharides (ALPs) from the Arctium lappa L. roots, the optimal extraction conditions of crude ALPs were optimized by using the single-factor experiment and response surface method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Based on these results, JFP-Ps show promise as a natural compound for improving human intestinal health and may be used as a potential phytochemical for this purpose. Gao et al (1) extracted polysaccharides (ALPs) from Arctium lappa L. using an optimized aqueous two-phase system with specific conditions: polyethylene glycol (PEG) relative molecular weight of 6,000, PEG quality fraction of 25%, (NH 4 ) 2 SO 4 quality fraction of 18%, and extraction temperature of 80 • C. The extraction rate reached 28.83%. FTIR, SEM, and HPLC analyses revealed that ALPs were acidic heteropolysaccharides with uneven particle size distribution, irregular shape, and rough surface.…”
Section: Non-starch Polysaccharidesmentioning
confidence: 99%
“…Based on these results, JFP-Ps show promise as a natural compound for improving human intestinal health and may be used as a potential phytochemical for this purpose. Gao et al (1) extracted polysaccharides (ALPs) from Arctium lappa L. using an optimized aqueous two-phase system with specific conditions: polyethylene glycol (PEG) relative molecular weight of 6,000, PEG quality fraction of 25%, (NH 4 ) 2 SO 4 quality fraction of 18%, and extraction temperature of 80 • C. The extraction rate reached 28.83%. FTIR, SEM, and HPLC analyses revealed that ALPs were acidic heteropolysaccharides with uneven particle size distribution, irregular shape, and rough surface.…”
Section: Non-starch Polysaccharidesmentioning
confidence: 99%
“…Plant polysaccharides, also known as plant aggregate polysaccharides, are generally recognized as a healthy material to enhance disease resistance and reduce medication. Plant polysaccharides have health effects including immune regulation, hypoglycemia, and liver protection ( 5 7 ). To date, plant polysaccharides have been a research focus.…”
Section: Introductionmentioning
confidence: 99%